PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DAN KEPERCAYAAN DIRI SISWA MELALUI REALISTIC MATHEMATIC EDUCATION - Yanto Yanto; Jajang Rahmatudin; Rifqi Hidayat (Integral : Pendidikan Matematika, 2018)
The research is based on the law of mathematics conceps understanding and the less of the students’s activation in learning process. The research is Quasi Experimental research. The research design is used Nonequivalent Control Group Design and sample collection technique is SamplingPurposive. The sample of the research is the 7th qraders39 student class 7th E is classes eksperimental and 39 student class 7th D is classes control. The population in the research is the students of class SMPN 2 Kapetakan Kabupaten Cirebon, academic year 2016/2017 The instrument used in the research is mathematics concept understanding skill test and student’s observation sheet. Test of the difference of the average of post-test using the test of Independent Sample T-Test equals sig (1-tailed) score 0,001< 0,05 means H0 ejjected. And then the difference of the average using of N-gain using the test of Independent Sample t-test equals sig score (1-tailed) 0,000 < 0,05 means H0 ejjected. And then the test of the difference of the average of self confident using the test of mann whitney U test sig (1-tailed) score 0,0005< 0,05 means H0 ejjected. The research result shows that: (1). The improvement of mathematics conceps understanding skill which is using realistic mathematic educationis better than the students who are learning by conventional learning process. (2). self confident in those students who are learning by mathematic realistic mathematic educationis better than the students who are learning by conventional learning process. Key Words: Realistic mathematic education and mathematics concept understanding